BENTUK DAN FUNGSI TUTURAN EKSPRESIF DALAM BAHASA PRANCIS - Siti Perdi Rahayu (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2012)
This study aims to describe forms, meanings, and functions of expressive utterances in French. The data were collected through listening and note-taking. The forms were analyzed by means of a substitution method and the functions by means of a referential correspondence method. The results are as follows. First, the forms and meanings of expressive utterances include (a) literal direct speech acts, (b) literal indirect speech acts, (c) non-literal direct speech acts, and (d) non-literal indirect speech acts. Second, the functions of expressive utterances include (a) congratulating, (b) thanking, (c) expressing sympathy/condolences, (d) complimenting, (e) apologizing, (f) criticizing, (g) complaining, and (h) blaming.